Electroretinogram Changes Following Sequential Panretinal Photocoagulation for Proliferative Diabetic Retinopathy - Khojasteh H (Dove Medical Press, 2020)
Hassan Khojasteh,1 Rasoul Amini Vishte,2 Ali Mirzajani,2 Elias Khalili Pour,1 Fatemeh Bazvand,1 Hamid Riazi-Esfahani,1 Masoud Mirghorbani,1 Bobeck S Modjtahedi3– 5 1Department of Ophthalmology, Farabi Eye Research Center, Farabi Eye Hospital, Tehran University of Medical Sciences, Tehran, Iran; 2Department of Optometry, School of Rehabilitation Sciences, Iran University of Medical Sciences, Tehran, Iran; 3Department of Ophthalmology, Southern California Permanente Medical Group, Baldwin Park, CA, USA; 4Department of Research and Evaluation, Southern California Permanente Medical Group, Pasadena, CA, USA; 5Eye Monitoring Center, Kaiser Permanente Southern California, Baldwin Park, CA, USACorrespondence: Hassan Khojasteh Email khojaste_hasan@yahoo.comPurpose: To evaluate changes in electroretinogram (ERG) response over the course of multiple sessions of panretinal photocoagulation (PRP) in patients with proliferative diabetic retinopathy (PRP).Methods: A prospective cohort study of 11 patients with PDR who required PRP was conducted. PRP was completed over three sessions. Each patient had five ERGs done: baseline, 1 week after each PRP session, and 6 weeks after the last session of PRP. Dark-adapted 0.01 ERG, Dark-adapted 3 ERG, Dark-adapted 10 ERG, Light- adapted 3 ERG, and Light-adapted 30 Hz flicker ERG were done. The mean change in a- and b-wave amplitudes as well as implicit times compared to baseline was analyzed.Results: A significant reduction in peak amplitudes of both a- and b-waves and delay in latencies were observed in all responses (p< 0.05). The absolute amplitude reduction and delay in latency were higher for scotopic b-waves (p< 0.05). The root mean square (RMS) of Dark-adapted 10.0 ERG (p< 0.05) and total mean amplitude changes of a- and b-waves (p< 0.001) were reduced after each laser session; however, the magnitude of change was not different between the first, second, or third sessions of PRP, and each session showed a similar deterioration rate of ERG parameters comparing to each other (p=0.4 for RMS and p=0.2 for total mean amplitude changes). In addition, the results indicated recovery of the amplitude and latency of ERG waves after 6 weeks from the final treatment (p< 0.001) although not to baseline levels.Conclusion: ERG findings following PRP show reduced retinal function after each session which partially recovers by 6 weeks after the completion of therapy. Clinicians should be mindful of these changes when planning the treatment course for patients with PDR.Keywords: diabetic retinopathy, electroretinogram, panretinal photocoagulation, laser